PENGARUH SISTEM INFORMASI AKUNTANSI TERHADAP SISTEM PENGENDALIAN INTERNAL PENJUALAN PADA CV INSPORT - Yeniasari Rizkia Budi; Dinda Vernanda Sari (Jurnal Perspektif Manajerial dan Kewirausahaan (JPMK), 2022)
This research purpose to determine the effect of the accounting information system on the internal control system at CV Insport. This research is a quantitative research. The data used is primary data in the form of a questionnaire distributed to employees who use the company's information system at CV Insport. This questionnaire was distributed to 30 respondents. The analytical method used in this research is Simple Linear Regression Analysis using SPSS version 26. Based on research analysis results that have been carried out, it shows that the independent variable (Accounting Information System) has a positive and significant effect on the dependent variable (Internal Control System).